STRUKTUR KOMUNITAS POHON MANGROVE DI KAWASAN DESA BAGAN ASAHAN KECAMATAN TANJUNG BALAI KABUPATEN ASAHAN - Vaisal Raju Siahaan; Ewin Handoko; Welmar Olfan Basten Barat (Program Studi Pendidikan Biologi, 2022)
Mangrove forest is a plant that grows in coastal areas or in coastal areas, and estuarine areas that have an ecological function, namely as the last protector from the waves of sea water after coral reef ecosystems and seagrass ecosystems, as sediment catchers, foraging for fish, as fish spawning grounds and as fish breeding grounds. Research on the Community Structure of Mangrove Plants in the Bagan Asahan Village Area, Tanjung Balai District, Asahan Regency was conducted in August 2020 with the aim of knowing the structure of the mangrove community and environmental factors that affect the existence of mangrove plants in Bagan Asahan Village. The method used in observing the structure of the mangrove plant community is using the quadrant transect method by analyzing species density, relative density, species frequency, relative frequency, species dominance, relative dominance, and important value index at the tree level. Based on the results of the study, it was found that Avicennia marina, Bruguiera gymnorrhiza and Rhizopora apiculata had the highest INP at the tree level. Further research is needed on the structure of the mangrove community in the same place and with different stations so that the mangrove data can represent the entire area of Bagan Asahan Village. The author suggests to further preserve mangroves.